Large deviations and metastability - Olivieri, Enzo, 1945- (Cambridge University Press, 2005)
The book provides a general introduction to the theory of large deviations and a wide overview of the metastable behaviour of stochastic dynamics. Written to be accessible to graduate students, this book provides an excellent route into contemporary research.
Keywords: Large deviations.; Stability.; Grandes déviations.; Stabilité.; stability.; MATHEMATICS -- Probability & Statistics -- General.; Large deviations; Stability